2009
DOI: 10.1348/014466608x386099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring masculinities within men's identificatory imaginings of first‐time fatherhood

Abstract: The changing role and practices of men as fathers is a growing subject of interest and debate within academic and everyday responses to contemporary sociocultural change. Prompted by questions about the production of identities and masculinities that accompanies social change, this paper is a psychosocial exploration of the identificatory positionings that are apparent in men's talk of becoming first-time fathers. Our qualitative analysis draws on a sample of 30 heterosexual and variously skilled men aged betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 29 publications
6
84
1
9
Order By: Relevance
“…However, although men in the present study reported significant effects of the extra responsibility, they did not seem to view their fathering as compensatory mothering. This is in contrast to Finn and Henwood's (2009) UK study with 30 firsttime fathers (from normative contexts) who framed their highly involved and nurturing fathering as motherly-like paternity. Our participants rarely gendered roles but instead oriented to a shared parenting discourse (Vuori, 2009) wherein both genders are, in principle, equally capable of and responsible for, all aspects of parenting.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, although men in the present study reported significant effects of the extra responsibility, they did not seem to view their fathering as compensatory mothering. This is in contrast to Finn and Henwood's (2009) UK study with 30 firsttime fathers (from normative contexts) who framed their highly involved and nurturing fathering as motherly-like paternity. Our participants rarely gendered roles but instead oriented to a shared parenting discourse (Vuori, 2009) wherein both genders are, in principle, equally capable of and responsible for, all aspects of parenting.…”
Section: Discussioncontrasting
confidence: 71%
“…This is surprising given the emphasis in family research and UK policy on the importance of fathers to child and family wellbeing (e.g. Finn & Henwood, 2009;Gold & Adeyemi, 2013;Loehlin, Horn, & Ernst, 2010;Ramchandani, Domoney, Sethna, Psychogious, Vlachos et al, 2012). As Asmussen and Weizel (2010) wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Some women, instead, may persist with continuous full-time participation, returning soon after childbirth (Solera, 2009;Scott et al, 2009;Bettio et al, 2013). For men the main reasons for interruptions are still not family-related, having more to do with unemployment or training, although men's take up rates of leaves show signs of increase among younger generations, opening not only to new gender allocations but also to new gender and parenthood identities (Finn and Henwood, 2009;Ray et al, 2010;EIGE, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Este interés se ha traducido en la realización de estudios cualitativos longitudinales que se han enfocado en dar cuenta del proceso que viven los hombres al convertirse en padres (Barclay & Lupton, 1999;Deave & Johnson, 2008;Draper, 2003;Finn & Henwood, 2009;Henwood & Procter, 2003;Ives, 2014;Miller, 2011;Shirani, 2015). Una de las preguntas que se plantean estos estudios es si se ha producido en las últimas décadas una evolución desde un padre proveedor (centrado en el trabajo, distante y autoritario) hacia un 'nuevo padre' (involucrado en los cuidados, cercano y afectivo).…”
Section: Expectativas En Torno a La Paternidad: ¿Nuevos Padres?unclassified